Islamization in Haminjon: A Study of Business Morality in Batak Entrepreneurial Networks - Syahrial Arif Hutagalung; Gatot Teguh Arifyanto; Fauzan Ghafur; Rika Githamala Ginting; Yessi Kurnia Arjani Manik (KURAS Institute, 2025)
This study examines the interaction between Islamic values and Batak traditions in the business practices of Muslim entrepreneurs in North Sumatra, focusing on haminjon (frankincense), which holds both spiritual and economic significance for Batak society. Unlike previous research that rarely explores the integration of religion and custom in trade, this study employs a qualitative ethnographic approach. Fieldwork was conducted over three months (April–June 2025) in Doloksanggul and Balige, involving seven participants: three Batak Muslim entrepreneurs, two haminjon traders, one customary leader, and one local ustaz. Data were collected through interviews, observations, and document analysis, and examined using thematic coding to identify negotiation patterns between adat and Islam. The findings indicate that Islamization in this context does not occur through doctrinal enforcement but rather through moral diplomacy, ethical conduct, and everyday commercial practices. Muslim entrepreneurs continue to uphold kinship ties and customary obligations, while reinterpreting them through Islamic principles such as honesty, justice, rejection of usury, and social responsibility. Within this process, haminjon serves as both a cultural and economic bridge, shifting from a ritual object into a symbol of halal trade and moral integrity. Theoretically, this study proposes a contextual model of Islamic business ethics rooted in local values yet adaptable to cultural pluralism. Practically, it underscores trade as a medium of Islamization, showing that the integration of religion and tradition occurs through productive reinterpretation that strengthens collective identity and supports sustainable development.